Effect of Cashless Financial Services on Economic Growth in Kigali, Rwanda - Esperance, Mupenzi (International Journal of Scientific Research and Management (IJSRM), 2024)
The research aimed at assessing the effect of cashless financial services on economic Growth in Kigali, Rwanda. The study was conducted in Kigali Rwanda. The time was limited in the period of 2014-2022.Thestudy was guided by the following specific objectives upon which also the following research questions were derived: To evaluate the effect of internet banking on Economic Growth in Kigali, Rwanda. To establish the impact of mobile cards on Economic Growth in Kigali, Rwanda. To assess the effect of mobile wallets on Economic Growth in Kigali, Rwanda. To evaluate the effect on mobile money on Economic Growth in Kigali, Rwanda. The research employed the use of Focus Group as one of interview methods to collect data from respondents. Rwanda still faces less privacy, greater exposure to hacking, technological dependency, magnifying economic inequality, and more. The current study therefore sought to find out the effect of cashless financial services on economic growth in Kigali, Rwanda amidst of the highlighted challenges associated with the cashless society plan. The researcher collected data from employees of MTN Rwanda, Eco bank Rwanda, BK, BNR and beneficiaries of selected institutions. The research design included: questionnaires; interviews and documentation research techniques. The sample size of the study is210 participants from Bank of Kigali, Eco bank, telecommunication companies (MTN) including mobile money agents by means of purposive sampling. The researcher requested the selected institutions to allow their members to participate in the interview and an authority letter for data collection from the University was presented to selected Institutions. Confidentiality and privacy were observed during the interview process. The researcher allowed the respondents to be free when collecting the data, mentioning names was avoided as it could be considered as coercing the respondents. Data collected was analyzed using SPSS.